NPBWR1 and NPBWR2: Implications in Energy Homeostasis, Pain, and Emotion - Sakurai, Takeshi (Frontiers in Endocrinology, 2013)
Neuropeptide B/W receptor 1 (NPBWR1) and NPBWR2 had been known as orphan receptors GPR7 and 8, respectively. Endogenous peptide ligands of these receptors, neuropeptide B and neuropeptide W, were identified in 2002 and 2003 (1-3). These peptides have been implicated in regulation of feeding behavior, energy homeostasis, neuroendocrine function, and modulating inflammatory pain. In addition, strong and discrete expression of their receptors in the extended amygdala and bed nucleus of the stria terminalis suggests a potential role in regulating stress responses, emotion, anxiety and fear. Recent studies of NPB/NPW using both pharmacological and phenotypic analyses of genetically engineered mice as well as a human study support this hypothesis.